Retrospective analysis of low-dose methadone and QTc prolongation in chronic pain patients - Huh, Billy; Park, Chan-Hong (Korean journal of anesthesiology, 2010)
Methadone is a synthetic opioid that is widely used for the treatment of chronic pain. The association between methadone treatment and QT interval prolongation or which can lead to torsades de pointes has been confirmed with larger studies on high dose methadone. The aim of this study was to determine the effect of methadone on the QTc interval in patients, whether the daily dose of methadone should be lower than what has been previously investigated. A total of 130 patients were included, with 90 patients in the methadone group and 40 patients in the control group. For each ECG, heart rate, QT interval and corrected QT (QTc) interval were recorded. The patient demographics, methadone dose and serum level, duration of methadone use and past medical history were collected. The QTc interval was significantly longer in the treatment group than in the control group (443 +/- 30.0 ms versus 408 +/- 28.0 ms, respectively, P < 0.0001) and more patients in the treatment group had a QTc interval greater than 450 ms (36.7% versus 7.5%, respectively, P = 0.0005). The QTc interval was not associated with methadone dose P = 0.9278), serum level (P = 0.2256) or duration of treatment (P = 0.1822). This study has shown that methadone use is associated with longer QTc intervals, even among patients with daily doses of less than 80 mg. In this study, no correlation was found between QTc duration and methadone dose, serum levels or duration of use. However, the magnitude of the QTc interval was associated with female gender and the use of antidepressants.